2023
DOI: 10.1371/journal.pone.0287810
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sedentary behavior and pancreatitis risk: Mendelian randomization study

Abstract: Background Although observational studies have shown that physical activity is a protective factor for acute pancreatitis, the causal associations between PA/ sedentary behavior and acute pancreatitis (AP) and chronic pancreatitis (CP) remain unclear. Methods We used Mendelian randomization as a strategy to assess the causalities between exposures and outcomes by simulating randomized experiments with genetic variation. The collected genetic variants data of physical activity were from UK Biobank, the data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Mendelian randomization (MR) studies select genetic variants related to exposure factors as instrumental variables to eliminate systematic errors, and alleles are randomly assigned according to Mendel's second law at conception, similar to randomization. Controlled trials [4] .MR is often used to verify the impact of exposure factors on disease risk, and helps to deeply describe the genetic factors related to the disease. In recent years, more and more studies have found through MR that the onset of AP may be affected by genetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mendelian randomization (MR) studies select genetic variants related to exposure factors as instrumental variables to eliminate systematic errors, and alleles are randomly assigned according to Mendel's second law at conception, similar to randomization. Controlled trials [4] .MR is often used to verify the impact of exposure factors on disease risk, and helps to deeply describe the genetic factors related to the disease. In recent years, more and more studies have found through MR that the onset of AP may be affected by genetics.…”
Section: Introductionmentioning
confidence: 99%
“…1 Materials and methods 1.1 Research design MR uses genetic variants that are strongly correlated with exposure factors as instrumental variables to infer the causal relationship between exposure and outcomes. These instrumental variables need to meet three core assumptions:(1) Genetic variation has a strong correlation with exposure; (2) Genetic variation has nothing to do with the confounding factors of the exposure-outcome association; (3) Genetic variation can only affect outcome through exposure and not through other pathways [4] .SNPs with strong correlations were screened as instrumental variables to verify hypothesis (1).MR research follows the genetic law of "random allocation of parental alleles to offspring during meiosis". The effect of genetic variation is less affected by confounding factors such as acquired environment and socioeconomic status, and satis es hypothesis (2).When the instrumental variable affects the outcome through pathways other than "genetic variation-exposure factor-outcome", the genetic variation is considered to have pleiotropic effect, so the pleiotropic effect of SNP is tested to verify the hypothesis (3).…”
Section: Introductionmentioning
confidence: 99%
“…Stress also affects health outcomes by increasing the risk of cardiac diseases, obesity, and type 2 diabetes [11] which can be explained by the secretion of hormones, peptides, and neurotransmitters that are involved in the body’s response to stress especially if the stress is severe and prolonged. [12] Also, physical inactivity has a role in deteriorating health outcomes, increases the risk of obesity, [13] and poses a significant challenge in Saudi Arabia as its prevalence ranges from 43.3% to 99.5%, among the Saudi population. [14]…”
Section: Introductionmentioning
confidence: 99%